A NEW INSTRUMENT OF EVALUATION OF STRESSFUL SITUATIONS IN CAREGIVERS OF ALZHEIMER PATIENTS - Muela Martínez, José Antonio; Torres Colmenero, Carlos Jesús; Peláez Peláez, Eva Mª (Anales de Psicología / Annals of Psychology, 2002)
Here, it is introduced an Inventory of situations potentially stressful in caregivers of Alzheimer Patients. These situations have been taken from interviews to caregivers of Alzheimer Patients during the last four years, where it was evaluated different aspects related not only to problematic situations which are directily showed by patients (repetition of the same question, incontinence, unable to remind the caregivers..), but also to those situations from the own caregiver’s evaluation about the care (guilty feelings, loss of a loved person, intentionality in the patient’s behaviour). Eighty-nine caregivers of Alzheimer Patients filled in the Inventory. Those patients showed a moderate- severe deterior. A way of checking this was to evaluate the perceived burden, the behavioural alterations of the Alzheimer Patients and the caregiver’s health. The Results have showed significant correlations between this inventory and the rest of the measures. These results take us to consider this inventory as a good instrument to measure specifically some situations that are potentially stressful for the caregivers of Alzheimer Patients.